Equality, Efficiency, and Market Fundamentals: The Dynamics of International Medical-Care Reform - Cutler, David (Journal of Economic Literature, 2002)
McMillan and three anonymous referees for helpful comments, and to the National Institutes on Public opinion surveys uniformly show low support for medical care systems in developed countries. The longstanding conflict between equal access to care and efficient service provision partly explains this dissatisfaction. But the tradeoff is particularly acute in medical care, as new technologies developed over time have increased the cost of care and made the equity commitment even more expensive. Countries first dealt with rising costs by maintaining equal access and restricting total spending. Efficiency suffered, however. As a result, many countries are considering a move away from spending controls and towards incentive-based medical care reform.